Associations of Trauma Severity with Mean Platelet Volume and Levels of Systemic Inflammatory Markers (IL1β, IL6, TNFα, and CRP) - Baris Alper; Baris Erdogan; Mehmet Özgür Erdogan; Korkut Bozan; Murat Can (Mediators of Inflammation)
We investigated the associations of injury severity scores (ISSs) with the mean platelet volume, the serum levels of two interleukins (IL1β and IL6), and the serum levels of tumour necrosis factor-α (TNFα) and C-reactive protein (CRP). We sought to identify biochemical parameters that could be used as components of a new biochemical parameter-based ISS system. The levels of CRP, TNFα, IL1β, and IL6 differed significantly (all p values < 0.05) between severely injured patients and controls. The mean platelet volume (MPV) did not correlate with the ISSs (p > 0.05). The TNFα and IL6 levels were useful for determining the severity of injury, and the CRP level was elevated in all trauma patients but did not correlate with the ISS. The IL1β level was higher in the study group but did not increase as the ISS increased. IL6 and TNFα levels were higher in the study group and increased as the ISS increased. We found no significant difference between the trauma group and healthy individuals in terms of MPV values. IL6 and TNFα levels can be used to assess trauma severity. However, neither the MPV nor the CRP or IL1β level is useful for this purpose.